Development of a 600 joules small plasma focus as pulsed radiation source / Lee Seng Huat - Lee, Seng Huat (2011)
The work starts at developing a 600 joules small plasma focus based on previous experience and works on the 3 kJ plasma focus system [Lee et al. (1988), Favre et al. (1992), Moo et al. (1995), Yap et. al. (2005)]. The objectives of this project are two folds, first, to scale down the energy of the plasma focus device from kJ to few hundred joules; and second to develop the new system as a pulsed radiation source. The development and construction of the small Mather type plasma focus system employed a novel design with electrodes of 60 mm in length and without an insulator as the conventional plasma focus. The investigation of the discharges is focused on getting an optimum operating condition for plasma focus with reproducible radiation emission. Argon gas is used, while the operating pressures are varied to study the dynamics of the plasma focus as well as the radiation output. The plasma focus discharges have been investigated by using a Rogowski coil, resistive voltage divider, X-ray Detector (XRD), EUV detector and biased ion collectors, for the discharge current, discharge voltage, X-ray radiation output, EUV radiation output and ion beam output. Suitable condition has been identified at a low pressure regime of 9.0 × 10-3 mbar to 2.2 × 10-2 mbar of argon. Reproducible results with good plasma focus and radiation output are obtained. The plasma focus is observed consistently; with good reproducibility of above 80 % in this pressure range. Radiation emissions are mainly in the ultra soft X-ray to EUV region. A total EUV energy vary from 7.8 mJ to 275 mJ is obtained, which corresponds to a conversion efficiency of 0.0013 % to 0.046 %. The ultra-soft radiation and EUV are emitted during the plasma focus time, where the signals are coincide with the voltage spike. The best condition of focusing discharge is identified to be in a very narrow range of argon pressures of 1.0 - 1.8 × 10-2 mbar. The highest EUV energy output of 275 mJ is also obtained at about 1.6 × 10-2 mbar. In these pressures, the ion beams observed are relatively low in intensity. Conversely, the ion beam is found to increase at lower pressures. Energies of the ion beams measured are calculated based on the time of flight method. Argon ion beam with energy of 38 keV to 560 keV are obtained. It is also found that 9.0 × 10-3 mbar is the optimum argon pressure for high energetic ion beam production.